English Language Teachers’ Awareness of English as a Lingua Franca in Multilingual and Multicultural Contexts - Guerra, Luis (2020)
Today English has become the Lingua Franca or common language of many people, regardless of their being native or nonnative speaker of English all over the world. Therefore, it has become necessary to educate pre-/in-service teachers with an awareness towards the significance of the involvement of an “English as a lingua franca” (ELF) perspective in their language teaching practice in multilingual/multicultural contexts. In a rapidly changing world, many English language teachers and teacher trainers are cognizant of the impact of migration in their teaching contexts. However, it is still not very clear to what extent and in what context they are integrating ELF related issues in their language teaching practice. In this study, we make an attempt to unveil in-service teachers’ beliefs about ELF in pedagogical practice in three different countries – Poland, Portugal and Turkey. In order to do that we have adopted a questionnaire from an earlier study investigating the involvement of culture in ELT in expanding circle contexts. The findings of the study revealed that although teachers in these contexts are aware of the significance of the inclusion of an ELF-aware perspective in ELT, they are still hesitant about its applicability in their own teaching context. This study has implications for raising English language teachers’ awareness in conceptualizing how an ELF-aware pedagogical approach can be implemented in a multilingual/multicultural context.